Medication errors by caregivers in the homes of children discharged from a pediatric department in Ghana - George Tsey Sabblah; Florence van Hunsel; Katja Taxis; Mahama Duwiejua; Seth Kwaku Seaneke; Eugène van Puijenbroek (SAGE Publishing, 2024)
Background: Medication errors (MEs) by caregivers at home are a cause of morbidity and mortality, shortly after discharge from the hospital. Objectives: The objective of this study was to determine the rate and types of MEs at the homes of children discharged from a hospital in Ghana and to explore the factors associated with these errors. Design: This was a cross-sectional study of infants and children discharged from the hospital to review medication administration practices. Methods: Caregivers of children discharged from the hospital after at least 24 hours of admission were interviewed at their homes about medication administration practices. The study assessed potential harm associated with MEs made by caregivers using the Harm Associated with Medication Error Classification tool. The Least Absolute Shrinkage and Selection Operator regression were used to identify the variables associated with MEs. Results: A total of 95 children (mean age: 28.6 months, 52.6% female) and their caregivers were included. Overall, 65 (68.4%) children experienced one or more MEs. Out of a total of 232 medications reviewed, 102 (44.0%) (95% CI: 37.6-50.4) were associated with a ME. The top two errors, wrong time errors and errors in the frequency of dosing were, 45.1% and 21.6%, respectively. Understanding the information on the disease condition being treated and the medicines dispensed was associated with committing fewer MEs. The number of medicines prescribed was associated with a higher likelihood of MEs. Out of 102 MEs, 48 (47.1%) were assessed as posing potentially no harm, 26 (25.5%) minor harm, 15 (14.7%) moderate harm, and 13 (12.8%) serious harm to the patients. Importantly, none of the MEs were assessed as posing potentially severe or life-threatening harm to the patients. Conclusion: MEs in children following discharge are high, and systems should be developed to prevent these errors.